Factors associated with the inter-facility transfer of inpatients in Sichuan province, China - Liu, Linxin (BMC Health Serv Res, 2019)
BACKGROUND: The overuse of tertiary hospitals and underuse of primary care facilities has been one of the key reasons leading to fast health expenditure increase and health service utilization inequity in China. Recent health care reform in China tries to enforce a patient transfer system to make the health services utilization more efficient. This study examined the pattern and associated factors of inter-facility transfer of inpatients in Sichuan province of Western China. METHODS: Patient discharge records (n = 1,490,695) from 604 general hospitals during the period of April to June 2015 in Sichuan were extracted from the front page of the medical records system with individual information on demographics, insurance coverage, diagnoses, hospitals admitted and discharge type. We calculated the percentage of inpatients transferring to other health facilities, the Inter-Facility Transfer Rate (IFTR) with adjustment for Charlson Comorbidity Index (CCI). Multi-level logistic regression models were established to identify factors associated with IFTRs. RESULTS: A small number of tertiary hospitals (n = 75, 12.41%) shared 51.71% (n = 770,823) of all admitted cases while a large number of primary/unrated hospitals (n = 321, 53.15%) shared only 8.15%. The overall CCI-adjusted IFTR was 2.08% with 3.73% among secondary hospitals, 1.87% among tertiary hospitals and 1.30% among primary/unrated hospitals. Uninsured patients (OR = 1.13) and those with a lower level of insurance entitlements (OR = 1.12 for the New Rural Cooperative Medical Scheme and the Basic Medical Insurance for Urban Residents) were more likely to experience inter-facility transfer than those with a higher level of insurance entitlements (the Basic Medical Insurance for Urban Employees). CONCLUSION: The level of IFTR in general hospitals in Sichuan is low, which is associated with the level of hospitals and insurance entitlements. Further studies are needed to better understand how patients and health care providers respond to different insurance policies and make decisions on inter-facility transfer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-019-4153-7) contains supplementary material, which is available to authorized users.